Biosynthesis of Nanoparticles Using Fungi and Their Effect on Plant Pathogenic Microorganisms: A sustainable ecofriendly Method . (International Journal of Food and Nutritional Sciences, 2023)
This research paper focuses on the biosynthesis of nanoparticles using fungi and their effect on plant pathogenic microorganisms. The study explores the use of fungi as a sustainable and eco-friendly method for synthesizing nanoparticles, with a particular focus on silver nanoparticles. The synthesized nanoparticles were characterized using various analytical techniques, including UV-visible spectroscopy, Fourier-transform infrared spectroscopy, and transmission electron microscopy. The antimicrobial activity of the synthesized nanoparticles was evaluated against three plant pathogenic microorganisms, namely, Fusarium oxysporum, Pythium ultimum, and Rhizoctonia solani. The results of the study indicate that the synthesized nanoparticles exhibited significant antimicrobial activity against the tested microorganisms. The findings of this study suggest that fungi-mediated nanoparticle synthesis can be a promising alternative to conventional methods and can have significant potential in the field of plant pathology.